PERLINDUNGAN HAK PEDIDIKAN BAGI PENYANDANG DIABILITAS DI SLB MAINNONG KECAMATAN DONRI-DONRI KABUPATEN SOPPENG - Andi Kasmawati; Mustari Mustari; Ira Mirwan (Jurnal Tomalebbi, 2023)
Abstract: This study aims to find out, (1) Theimplementation of the right to education of persons with disabilities in SLB Mainnong, Donri-Donri District, Soppeng Regency. (2) Factors affecting the fulfillment of the educational rights of persons with disabilities in SLB Mainnong, Donri-Donri District, Soppeng Regency. To achieve this goal, researchers use data collection techniques through documentation, observation, and interviews. The data obtained from the research results were obtained using qualitative analysis. The results of this study show that, (1) The fulfillment of the educational rights of persons with disabilities in SLB Mainnong, Donri-Donri District, Soppeng Regency has been fulfilled but has not been optimal. (2) Supporting factors in the fulfillment of the educational rights of persons with disabilities, namely the social environment conditions within the scope of the Mainnong Special School and also the physical environment conditions in the form of existing facilities and infrastructure. The inhibiting factor in the fulfillment of educational rights for persons with disabilities is the lack of awareness of the parents of students regarding the importance of education for students with disabilities. Then another obstacle is related to existing educators not meeting the academic qualifications of special education teachers as regulated in the Regulation of the Minister of National Education of the Republic of Indonesia Number 32 of 2008 concerning academic qualification standards and competencies of special education teachers.Keywords: Fulfillment, Right to Education, Persons with DisabilitieAbstrak: Penelitian ini bertujuan untuk mengetahui, (1) Pemenuhan hak pendidikan penyandang disabilitas di SLB Mainnong Kecamatan Donri-Donri Kabupaten Soppeng. (2) Faktor yang mempengaruhi pemenuhan hak pendidikan penyandang disabilitas di SLB Mainnong Kecamatan Donri-Donri Kabupaten Soppeng. Untuk mencapai tujuan tersebut maka peneliti menggunakan teknik pengumpulan data melalui, dokumentasi, observasi, dan wawancara. Data yang diperoleh dari hasil penelitian dioleh dengan menggunakan analisis kualitatif. Hasil penelitian ini menunjukkan bahwa, (1) Pemenuhan hak pendidikan penyandang disabilitas di SLB Mainnong Kecamatan Donri-Donri Kabupaten Soppeng telah terpenuhi namun belum optimal. (2) Faktor pendukung dalam pemenuhan hak pendidikan penyandang disabilitas yakni kondisi lingkungan sosial di lingkup SLB Mainnong dan juga kondisi lingkungan fisik berupa sarana dan prasarana yang ada. Adapun faktor penghambat dalam pemenuhan hak pendidikan bagi penyandang disabilitas yaitu kurangnya kesadaran orang tua dari peserta didik terkait pentingnya pendidikan bagi peserta didik penyandang disabilitas. Kemudian yang menjadi kendala lain terkait dengan tenaga pendidik yang ada tidak memenuhi kualifikasi akademik guru pendidikan khusus yang diatur dalam Peraturan Menteri Pendidikan Nasional Republik Indonesia Nomor 32 Tahun 2008 tentang standar kualifikasi akademik dan kompetensi guru pendidikan khusus.Kata Kunci:Pemenuhan, Hak Pendidikan, Penyandang Disabilitas